Establishment of A Transient Expression Using PEG-Mediated Protoplast Transformation System in Black Rice Cempo Ireng - Rahayu Opi Anggoro (Journal of Biotropical Research and Nature Technology, 2023)
Indonesia black rice is a potential crop which consider to be develop as functional food because of high nutritional values. However, some agronomical traits, such as high culm and long harvesting time need to be improved for high productivity. Genetic engineering based on protoplast system is one of tools that can be used for improving black rice agronomical traits. The purpose of this study was to establish an efficient method for obtaining protoplasts, and to get information on whether the PEG-mediated transformation method can be carried out on black rice ‘Cempo Ireng’ using GFP transient expression as a marker. To get protoplast culture, we used callus and seedling as main explants. The results showed that 15th days seedling was the best explant source to get protoplast compare to callus. The combination of 1,5% macerozyme and 3% celulase was optimum to obtain the viable protoplasts. Transient expression of GFP can be done using PEG-mediated protoplast transformation in 30% concentration of PEG.